2019
DOI: 10.1002/mds.27935
|View full text |Cite
|
Sign up to set email alerts
|

Salivary microR‐153 and microR‐223 Levels as Potential Diagnostic Biomarkers of Idiopathic Parkinson's Disease

Abstract: Background Parkinson's disease (PD) is the most common movement disorder among adults, affecting 2% of the world population older than 65 years of age. No diagnostic biomarker for routine use in clinical settings currently exists. Dysregulation of microRNAs (miRNAs) has been implicated in various neurodegenerative conditions, including PD. Distinct miRNAs have been demonstrated to be involved in the regulation of α‐synuclein, a key player in PD pathogenesis; miR‐153 and miR‐223 are downregulated in the brain a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
84
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(86 citation statements)
references
References 61 publications
0
84
2
Order By: Relevance
“…Emerging studies have shown the differential expression of miRNAs in blood between patients with PD and healthy controls. The expression levels of miRNAs, including Homo sapiens (hsa)-miR-7-5p, hsa-miR-22-3p, hsa-miR-136-3p, hsa-miR-139-5p, hsa-miR-330-5p, hsa-miR-433-3p, hsa-miR-495-3p (Ravanidis et al, 2019), hsa-miR-27a (Chen et al, 2018), hsa-miR-137 (Li et al, 2017), hsa-miR-331-5p (Cardo et al, 2013), hsa-miR-19b-3p (Uwatoko et al, 2019), hsa-miR-520d-5p (Jin et al, 2018), hsa-miR-195 (Ding et al, 2016), hsa-miR-29a-3p, hsa-miR-30b-5p, hsa-miR-103a-3p (Serafin et al, 2015), and hsa-miR-105-5p (Yang et al, 2019a), were up-regulated, while hsa-let-7a, hsa-let-7f, hsa-miR-142-3p, hsa-miR-222 (Chen et al, 2018), hsa-miR-433, hsa-miR-133b (Zhang et al, 2017), hsa-miR-671-5p (Uwatoko et al, 2019), hsa-miR-141, hsa-miR-214, hsa-miR-146b-5p, hsa-miR-193a-3p , hsa-miR-29 (Bai et al, 2017), hsa-miR-15b, hsa-miR-181a, hsa-miR-185, hsa-miR-221 (Ding et al, 2016), hsa-miR-153, hsa-miR-223 (Cressatti et al, 2019), and hsa-miR-133b (Zhao et al, 2014) were found to be down-regulated in the blood of patients with PD compared with that of healthy controls (Figure 1). Hsa-miR-7 is down-regulated in the peripheral blood and regulates the expression of brain-derived neurotrophic factor (BDNF) through an auto-regulatory mechanism.…”
Section: Blood Mirnas and Pdmentioning
confidence: 99%
“…Emerging studies have shown the differential expression of miRNAs in blood between patients with PD and healthy controls. The expression levels of miRNAs, including Homo sapiens (hsa)-miR-7-5p, hsa-miR-22-3p, hsa-miR-136-3p, hsa-miR-139-5p, hsa-miR-330-5p, hsa-miR-433-3p, hsa-miR-495-3p (Ravanidis et al, 2019), hsa-miR-27a (Chen et al, 2018), hsa-miR-137 (Li et al, 2017), hsa-miR-331-5p (Cardo et al, 2013), hsa-miR-19b-3p (Uwatoko et al, 2019), hsa-miR-520d-5p (Jin et al, 2018), hsa-miR-195 (Ding et al, 2016), hsa-miR-29a-3p, hsa-miR-30b-5p, hsa-miR-103a-3p (Serafin et al, 2015), and hsa-miR-105-5p (Yang et al, 2019a), were up-regulated, while hsa-let-7a, hsa-let-7f, hsa-miR-142-3p, hsa-miR-222 (Chen et al, 2018), hsa-miR-433, hsa-miR-133b (Zhang et al, 2017), hsa-miR-671-5p (Uwatoko et al, 2019), hsa-miR-141, hsa-miR-214, hsa-miR-146b-5p, hsa-miR-193a-3p , hsa-miR-29 (Bai et al, 2017), hsa-miR-15b, hsa-miR-181a, hsa-miR-185, hsa-miR-221 (Ding et al, 2016), hsa-miR-153, hsa-miR-223 (Cressatti et al, 2019), and hsa-miR-133b (Zhao et al, 2014) were found to be down-regulated in the blood of patients with PD compared with that of healthy controls (Figure 1). Hsa-miR-7 is down-regulated in the peripheral blood and regulates the expression of brain-derived neurotrophic factor (BDNF) through an auto-regulatory mechanism.…”
Section: Blood Mirnas and Pdmentioning
confidence: 99%
“…Different miRNA profiles are found in PD and other neurodegenerative disorders, with increased expression of miR-30a-5p, miR-153, and miR-4639-5p being identified in PD compared with unaffected healthy individuals. [232][233][234] Thus, it is likely that, in the near future, the application of miRNA panels on body-fluids such as a serum, saliva, and cerebrospinal fluid may provide potential PD diagnostic biomarkers, and may also help stratify PD patients according to the genetic and molecular pathways involved.…”
Section: Mirna Therapeuticsmentioning
confidence: 99%
“…In addition, unlike the application of miRNAs therapeutics in liver disease, where miRNA mimics or antimiRs may readily enter the target tissue and exert their effects, 230 difficulties in miRNA delivery across the blood–brain barrier is one of the factors that limit the progress in miRNA‐based therapeutics 231 and other therapeutic nucleic acids. Different miRNA profiles are found in PD and other neurodegenerative disorders, with increased expression of miR‐30a‐5p, miR‐153, and miR‐4639‐5p being identified in PD compared with unaffected healthy individuals 232–234 . Thus, it is likely that, in the near future, the application of miRNA panels on body‐fluids such as a serum, saliva, and cerebrospinal fluid may provide potential PD diagnostic biomarkers, and may also help stratify PD patients according to the genetic and molecular pathways involved.…”
Section: Nucleic Acid Therapeutics and Its Progress In Pd Researchmentioning
confidence: 99%
“…Recent studies have also shown that saliva can be used as a non-invasive source to detect the change in expression of circulatory miRNAs in patients with PD as compared to controls. Using saliva samples from 83 PD patients and 77 non-neurological controls, Cressatti et al showed that miR-153 and miR-223 expression levels were significantly downregulated in PD vs. controls [56]. Another RT-qPCR based study on saliva samples from 30 PD patients vs. 30 healthy controls revealed the increased expression of miR-874 and miR-145-3p in PD patients as compared to controls.…”
Section: Introductionmentioning
confidence: 99%